Health Education About The Dangers of Free Sex at Senior High School 22 Maluku - Nanlohy, Wildia; Wakano, Melawati; Tihurua, Ma'syari Arfah; Corputty, Lintje Sintje; Thalib, Abdul (Journal of Evidence-Based Community Health, 2024)
Free sex behavior among adolescents is a global issue that requires serious attention in efforts to prevent sexually transmitted diseases (STDs) and unwanted pregnancies . The results of the study on the effectiveness of interventions in increasing the knowledge of abdimas participants about the topics discussed. Results showed a significant increase from 38.2% to 88.2% in the number of abdimas participants who had good knowledge after the intervention. Some of the factors contributing to this increase include interactive and structured outreach methods, as well as participant involvement in intervention activities. Social interaction and exchange of experiences are also considered to play an important role in enriching participants' understanding. Although knowledge is the first step, behavior change requires consideration of other factors such as attitudes, social norms, and the environment. The integration of these components in intervention programs can amplify the positive effects of increased knowledge.